STUDI KRITIK MELALUI METODE TAKHRIJ HADITS TENTANG MENGHIAS BANGUNAN MASJID SEBAGAI TANDA AKHIR ZAMAN - Abdillah, Junaidi (JURNAL AL-IJTIMAIYYAH, 2018)
This paper aims to explore and reveal the law (istimbāth al-ahkām) about the law of boast and decorate the building of the mosque. The theme in this paper becomes an important and interesting issue when faced with contemporary phenomenon in Indonesia in particular and massively world, many people who build and decorate the mosque. Though normatively, this practice allegedly the Prophet as a sign of the end of time. This paper is written using syarah and naqd through out methods takhrij al-hadits approach. While in the realm of legal extraction, the approach used is a hermeneutical approach based on qawa’id al-lughawiyyah and maqashid al-syari’ah on texts of hadith. This study produces several conclusions: (1) hadith about proudly with mosque belonging to Āhād hadith category which is zhanni al-wurud (2) The law of building and decorating the mosque is makruh li-tahrim notes not accompanied by efforts to revive and prosper the mosque (3) This hadith include a hunching hadith containing a profound message of will as a stimulus of the Prophet SAW to his people aware of the existence, purpose, orientation of building the mosque itself and the existence of accountability in the hereafter.Key words: Mosque, splendor, doomsday, decorate, law